2019
DOI: 10.1101/864306
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Attraction, Dynamics, and Phase Transitions in Fire Ant Tower-Building

Abstract: Many insect species, and even some vertebrates, assemble their bodies to form multi-functional materials that combine sensing, computation, and actuation. The tower-building behavior of red imported re ants, Solenopsis invicta, presents a key example of this phenomenon of collective construction. While biological studies of collective construction focus on behavioral assays to measure the dynamics of formation and studies of swarm robotics focus on developing hardware that can assemble and interact, algorithms… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…This activity endows unperturbed fire ants with the ability to dynamically change their raft shapes [ 19 ] and even form complex, three-dimensional (3D) structures such as towers nucleated about substrates [ 20 ]. While the behaviour and flow of 3D ant towers has been examined [ 20 , 21 ], questions remain regarding the long-term dynamics of approximately two-dimensional (2D) rafts. Mlot et al [ 11 ] reported that, upon being placed into the water as approximately 3D spheroids, ant rafts spread out rapidly.…”
Section: Introductionmentioning
confidence: 99%
“…This activity endows unperturbed fire ants with the ability to dynamically change their raft shapes [ 19 ] and even form complex, three-dimensional (3D) structures such as towers nucleated about substrates [ 20 ]. While the behaviour and flow of 3D ant towers has been examined [ 20 , 21 ], questions remain regarding the long-term dynamics of approximately two-dimensional (2D) rafts. Mlot et al [ 11 ] reported that, upon being placed into the water as approximately 3D spheroids, ant rafts spread out rapidly.…”
Section: Introductionmentioning
confidence: 99%